Synthesis, Crystal Structures, and Properties of (4, 4'‐Hbipy)2[Sn2(C2O4)3] and (4, 4'‐Hmbipy)[SnX2] (X = C2O42–, m = 2; X = Cl, m = 0; bipy = bipyridine). Issue 5 (3rd March 2020) - Li, Yalan; Wu, Yuandong; Mei, Dajiang; Doert, Thomas
Abstract : Three new tin coordination compounds (4, 4'‐Hbipy)2 [Sn2 (C2 O4 )3 ] (1 ), (4, 4'‐H2 bipy)[Sn(C2 O4 )2 ] (2 ), and SnCl2 (4, 4'‐bipy) (3 ) were synthesized under hydro‐(solvo‐)thermal conditions and their crystal structures were determined by single‐crystal X‐ray diffraction. Compound 1 exhibits a ionic structure based on discrete [4, 4'‐Hbipy] + cations and [Sn2 (C2 O4 )3 ] 2– anions. These two units are linked via N–H··· O hydrogen bonds to form a pseudo‐one‐dimensional zigzag hydrogen‐bonded chain. In compound 2, four‐coordinate Sn atoms form monomeric tin dioxalato complexes, which are connected to the doubly protonated [4, 4'‐H2 bipy] 2+ cations through N–H··· O hydrogen bonded to give a one‐dimensional zigzag hydrogen‐bonded chain. Compound 3 forms a three‐dimensional hydrogen‐bonded network, in which 1 ∞ [SnCl2 (4, 4'‐bipy)] linear chains are interconnected to each other by C–H··· Cl hydrogen bonding. The solid‐state UV/Vis/NIR diffuse reflectance spectroscopy shows that three compounds are broadband semiconductors. The thermogravimetric analysis evidences the thermal stability of the three compounds up to 175, 201, and 246 °C, respectively. Abstract :